2020
DOI: 10.1002/cam4.2833
|View full text |Cite
|
Sign up to set email alerts
|

Identification of three m6A‐related mRNAs signature and risk score for the prognostication of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most common type of liver cancer and is extremely harmful to human health. In recent years, N6‐methyladenosine (m6A) RNA methylation in eukaryotic mRNA has been increasingly implicated in cancer pathogenesis and prognosis. In this study, we downloaded the expression profile and clinical information of 307 patients from The Cancer Genome Atlas database and 64 patients from the Gene Expression Omnibus (GEO) database, and univariate Cox analysis revealed that METTL14 was a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 36 publications
4
51
0
Order By: Relevance
“…Besides, the "erasers" comprise fat mass and obesity-associated protein (FTO) and alkB homolog 5 (ALKBH5) (Jia et al, 2011;Zheng et al, 2013). Various studies have revealed that m6A regulators can be used as novel prognostic biomarkers in different types of cancer (Chen et al, 2019;Fang and Chen, 2020;Huang et al, 2020a;Li Z. et al, 2020;Lu et al, 2020). METTL3 was shown to promote the proliferation and migration of hepatocellular carcinoma via the YTHDF2-dependent pathway and its knockdown could inhibit tumor progression (Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the "erasers" comprise fat mass and obesity-associated protein (FTO) and alkB homolog 5 (ALKBH5) (Jia et al, 2011;Zheng et al, 2013). Various studies have revealed that m6A regulators can be used as novel prognostic biomarkers in different types of cancer (Chen et al, 2019;Fang and Chen, 2020;Huang et al, 2020a;Li Z. et al, 2020;Lu et al, 2020). METTL3 was shown to promote the proliferation and migration of hepatocellular carcinoma via the YTHDF2-dependent pathway and its knockdown could inhibit tumor progression (Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies showed that m 6 A RNA methylation played a role in the occurrence and progression of multiple malignant tumors, including hepatocellular carcinoma, colorectal carcinoma, breast cancer, glioblastoma and clear cell renal cell carcinoma [12][13][14][15]. Yongsheng li et al have concluded the characteristics of m 6 A RNA methylation across 33 types of cancer and predicted that the mechanism of m 6 A RNA modification might be related with the activation or depression of some oncogenic pathways such as PI3K-AKT-mTOR signaling, G2M checkpoint, KRAS and P53 pathways [16].…”
Section: Introductionmentioning
confidence: 99%
“…Increased METTL14 expression inhibited the ability of migration and invasion in vitro tumor cell (41). METTL14 may play a role in the progression of HCC by regulating the m6A levels of CSAD, GOT2, and SOCS2 (42). In this study, we also found that KIAA1429 protein expression was not detected in normal liver tissues and HCC tissues.…”
Section: Discussionmentioning
confidence: 50%